2009
DOI: 10.1007/s10764-009-9352-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Site Fidelity and Individual Home Range Shifts in Lophocebus albigena

Abstract: We investigated long-term site fidelity of gray-cheeked mangabey (Lophocebus albigena) groups in Kibale National Park, Uganda. Concurrently, we monitored shifts in home range by individual females and subadult and adult males. We documented home range stability by calculating the area of overlap in successive years, and by recording the drift of each group’s monthly centroid from its initial location. Home ranges remained stable for 3 of our 4 groups (overlap over 10 yr >60%). Core areas were more labile, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 81 publications
2
58
0
Order By: Relevance
“…Recent studies examining home range stability within primates have focused on the role of resource distribution [Asensio et al, 2012;Ramos-Fernandez et al, 2013;Wallace, 2006] and individual knowledge of the home range [Brockelman, 2009;Janmaat et al, 2009]. For many of these studies, observers have found that primates shift their home range activities in response to changing ecological conditions, demonstrating considerable differences in areas of short-term use while maintaining fairly high stability in long-term home range size and location [Janmaat et al, 2009;Ramos-Fernandez et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies examining home range stability within primates have focused on the role of resource distribution [Asensio et al, 2012;Ramos-Fernandez et al, 2013;Wallace, 2006] and individual knowledge of the home range [Brockelman, 2009;Janmaat et al, 2009]. For many of these studies, observers have found that primates shift their home range activities in response to changing ecological conditions, demonstrating considerable differences in areas of short-term use while maintaining fairly high stability in long-term home range size and location [Janmaat et al, 2009;Ramos-Fernandez et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…For many of these studies, observers have found that primates shift their home range activities in response to changing ecological conditions, demonstrating considerable differences in areas of short-term use while maintaining fairly high stability in long-term home range size and location [Janmaat et al, 2009;Ramos-Fernandez et al, 2013]. Furthermore, it has been argued that home range stability may be maintained due not only to the predictability of food resources but also the benefits of spatial information in general, including knowledge of efficient travel routes, safe escape routes, and relationships with neighboring conspecifics [Bartlett, 2002;Fuentes, 2000;Janmaat et al, 2009;Wallace, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the overlapping areas between pairs of successive periods (e.g., months, years) to investigate site fidelity [e.g., Asensio et al, 2012b;Janmaat et al, 2009;Young et al, 2006;Young et al, 2008]. RamosFernandez et al [2013] proposed an estimate of site fidelity based on the recurrent use of particular areas across all (not just successive) periods.…”
Section: Home Range and Core Area Fidelitymentioning
confidence: 99%
“…Several studies have measured site fidelity across multiple taxa [Asensio et al, 2012b;Burdett et al, 2007;Cords, 1987;Easley & Kinzey, 1986;Hellickson et al, 2008;Janmaat et al, 2009;Kitchen et al, 2000;Switzer, 1993]. Some authors consider that strong site fidelity reflects spatial stability in the location of resources for an animal over time whereas weak fidelity is the result of temporal shifts in the spatial distribution of resources [Doncaster & Macdonald, 1991;Kie et al, 2010;Rivrud et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation